2020
DOI: 10.1111/andr.12868
|View full text |Cite
|
Sign up to set email alerts
|

Why does COVID‐19 kill more elderly men than women? Is there a role for testosterone?

Abstract: Background Recent epidemiological data indicate that there may be a gender predisposition to COVID‐19, with men predisposed to being most severely affected, and older men accounting for most deaths. Objectives Provide a review of the research literature, propose hypotheses and therapies based on the potential link between testosterone (T) and COVID‐19 induced mortality in elderly men. Materials and Methods A search of publications in academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 108 publications
(206 reference statements)
4
82
0
6
Order By: Relevance
“…Several studies have indeed reported androgendependent upregulation of ACE2 and TMPRSS2 proteins in normal prostate tissue, prostate cancer cell lines, and lung cancer cell lines. [18][19][20][21][22][23][41][42][43] However, multiple studies have shown no differences between males and females in ACE2 and TMPRSS2 mRNA or protein expression in human or murine lung tissue, indicating that T is unlikely to upregulate these gene products in lung, [44][45][46][47][48][49] using a microarray gene expression data set generated from bronchial brushings of 504 healthy subjects reported that gender did not correlate with gene expression of any candidate host molecule involved in COVID-19 infection, and that ACE2 and TMPRSS2 were the lowest expressed genes of interest among those examined. 49 The authors suggested that alternative mechanisms in the respiratory mucosa may become important during COVID-19 infection, perhaps including other coreceptors.…”
Section: Deaths In Different States Within the United Statesmentioning
confidence: 99%
“…Several studies have indeed reported androgendependent upregulation of ACE2 and TMPRSS2 proteins in normal prostate tissue, prostate cancer cell lines, and lung cancer cell lines. [18][19][20][21][22][23][41][42][43] However, multiple studies have shown no differences between males and females in ACE2 and TMPRSS2 mRNA or protein expression in human or murine lung tissue, indicating that T is unlikely to upregulate these gene products in lung, [44][45][46][47][48][49] using a microarray gene expression data set generated from bronchial brushings of 504 healthy subjects reported that gender did not correlate with gene expression of any candidate host molecule involved in COVID-19 infection, and that ACE2 and TMPRSS2 were the lowest expressed genes of interest among those examined. 49 The authors suggested that alternative mechanisms in the respiratory mucosa may become important during COVID-19 infection, perhaps including other coreceptors.…”
Section: Deaths In Different States Within the United Statesmentioning
confidence: 99%
“…First, chronic airway disease, smoking, and pollution are associated with expansion of the population of alveolar macrophages expressing ACE2 ( Abassi et al, 2020d ). Furthermore, ACE2 expression is increased in males ( La Vignera et al, 2020 ; Papadopoulos et al, 2020 ). Indeed, bioinformatics analyses revealed higher abundance of ACE2-expressing AT2 cells in men than women ( Wei et al, 2020 ), potentially enhancing viral susceptibility among men.…”
Section: Ace2 and Sars-cov-2 Associationmentioning
confidence: 99%
“…In addition, testosterone enhances AT1R expression in male, whereas estrogen preferentially upregulates AT2R expression in females ( Chanana et al, 2020 ). Finally, hypogonadal males are characterized by low T cell count which may provide unrestrained environment for severe responses to SARS-CoV-2 infection ( Papadopoulos et al, 2020 ). In sum, it is tempting to assume that enhanced expression of ACE2 in target organs and also of other molecules permissive to viral binding to ACE2 facilitate viral invasion and augment viral load ( Figure 3 ), although the details of this formulation require validation in further studies.…”
Section: Ace2 and Sars-cov-2 Associationmentioning
confidence: 99%
“…Importantly, this ACE2 and TMPRSS2 up-regulation was also associated with the up-regulation of the androgen pathway, suggesting that the smoking-mediated increased activity of the androgen signaling pathway itself and up-regulation of the central regulators of androgen pathways (e.g., HDAC6, CTNNB1, and SMARCA4) paired with the increased ACE2 and TMPRSS2 expression could represent a mechanism for the increased susceptibility of smokers to SARS-CoV-2 [ 295 ]. Importantly, the opportunity for SARS-CoV-2 infection of being androgen-mediated [ 296 ] via the androgen receptor-TMPRSS2 link, where the transcription of the TMPRSS2 is controlled by the androgen receptor activity [ 297 ], can represent a mechanistic explanation for the known sex-related differences in the COVID-19 vulnerability and lethality, with males typically being more susceptible to the infection [ 298 , 299 , 300 ]. This also suggests that androgen deprivation therapy, leading to the reduction of the TMPRSS2 expression, thereby limiting SARS-CoV-2 cellular entry, could potentially protect against severe complications from COVID-19 [ 301 , 302 , 303 ].…”
Section: Human (Host) Factorsmentioning
confidence: 99%